Fundamentals of molecular spectroscopy - Banwell, C. N. (McGraw-Hill, 1994)
This revision of Dr. Branwell's highly popular text retains the features which have made it so attractive to students and lecturers over the years. It remains an elementary and non-mathematical introduction to molecular spectroscopy that emphasizes the overall unity of the subject and offers a pictorial perception rather than a mathematical description of the principles of spectroscopy.